Improved Effectiveness of Combined Screening for Multiple Cancers: A Government‐Organized Population‐Based Study in China - Qian Lu; Di Liang; Jin Shi; Siqi Wu; Xinyu Du; Yutong He (Cancer Medicine)
ABSTRACT Objective The purpose of this study was to analyze the effectiveness of the Cancer Screening Program in Urban China (CanSPUC) in Hebei Province, 2016–2023. Methods A questionnaire for risk factors of lung, breast, upper gastrointestinal, liver, and colorectal cancers was administered to urban residents aged 40–74 years in five cities to assess their cancer risk. High‐risk participants were invited for screening and classified into five groups on the basis of the number of cancer types that were assessed to be high risk. The participation and positive outcome rates were analyzed. The incidence and the mortality of five types of cancer and all‐cause mortality of the screened and nonscreened participants were calculated via inverse probability weighting. Results A total of 237,975 eligible participants were enrolled in our study and 118,339 participants (49.94%) were assessed to be at high risk for one or more of the five cancer types. The number of screenings performed was 103,824, with a screening participation rate of 40.49%. Among the 57,315 screening participants, 9077 (15.84%) had positive cancer diagnoses and 871 (1.52%) were diagnosed with suspected cancer. Compared with the participants at high risk for a single cancer type, the participation and positive outcome rate increased by 45% and 71.5% in the participants at high risk for multiple cancer types. Compared with the non‐screened participants, the screened participants had a 27.0% decrease in mortality due to the five types of cancer and a 45.8% decrease in all‐cause mortality. Conclusion A combined screening program for multiple cancers could increase participation and positive outcome rates. It could also decrease the five types of cancer mortality and all‐cause mortality. Our findings highlight the effectiveness of combined screening for multiple cancers with limited health care resources, and may provide foundational evidence for the feasibility of conducting combined screening programs.